2021
DOI: 10.1038/s41368-021-00136-2
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis exacerbates ulcerative colitis via Porphyromonas gingivalis peptidylarginine deiminase

Abstract: Ulcerative Colitis (UC) has been reported to be related to Porphyromonas gingivalis (P. gingivalis). Porphyromonas gingivalis peptidylarginine deiminase (PPAD), a virulence factor released by P. gingivalis, is known to induce inflammatory responses. To explore the pathological relationships between PPAD and UC, we used homologous recombination technology to construct a P. gingivalis strain in which the PPAD gene was deleted (Δppad) and a Δppad strain in which the PPAD gene was restored (comΔppad). C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Histological activity index grading is assessed by epithelium (0, normal morphology; 1, minimal loss of goblet cells; 2, extensive loss of goblet cells; 3, loss of crypts; 4, loss of crypts in large areas) and infiltration (0, no infiltrate; 1, infiltrate around the crypt base; 2, infiltrate in the muscularis mucosa; 3, extensive infiltrate in the muscularis mucosa with edema; 4, infiltration in the submucosa). 37…”
Section: Histological Analysismentioning
confidence: 99%
“…Histological activity index grading is assessed by epithelium (0, normal morphology; 1, minimal loss of goblet cells; 2, extensive loss of goblet cells; 3, loss of crypts; 4, loss of crypts in large areas) and infiltration (0, no infiltrate; 1, infiltrate around the crypt base; 2, infiltrate in the muscularis mucosa; 3, extensive infiltrate in the muscularis mucosa with edema; 4, infiltration in the submucosa). 37…”
Section: Histological Analysismentioning
confidence: 99%
“…found that P. gingivalis exacerbated the severity of UC, in part through Porphyromonas gingivalis peptidylarginine deiminase (PPAD). The main mechanisms are stimulation of Th17 numbers and IL-17 production, and reduction of Treg numbers and IL-10 production ( Zhao et al., 2021 ). According to a recent study, P. gingivalis modifies the gut microbiota, which eventually stimulates intestinal IL-9+CD4+T cells and inflammation ( Sohn et al., 2022 ).…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Klebsiella strains isolated from the salivary microbiota with multidrug resistance were capable of colonizing the colon and increasing the numbers of proinflammatory TH1 cells, which subsequently aggravated the progression of IBD [ 104 ]. In addition, PADs, an enzyme or virulence factor specific to P. gingivalis , promotes the production of Th17 cells and IL-17, causing aggravation of UC [ 144 ]. It has been demonstrated that P. gingivalis dramatically increases the severity of colitis by breaking down TJPs to increase the permeability of the intestinal epithelium [ 145 ].…”
Section: Introductionmentioning
confidence: 99%